The systems psychodynamic leadership coaching experiences of nursing managers - Frans Cilliers; Landa Terblanche (AOSIS, 2010)
The mostly linear and mechanistic nature of the nursing manager role is rapidly becoming more dynamic and systemic. The change involves task and people management within a constantly changing organisational identity, taking up multiple leadership roles, having to authorise oneself and others in a complex matrix system, and managing conscious and unconscious psychological boundaries within and between conflicting systems. The aim of this study was to describe the systems psychodynamic learning experiences of nursing managers during leadership coaching. The coaching task was to provide learning opportunities to the individual leader, towards gaining insight into conscious and unconscious leadership dynamics in terms of anxiety, task, role, authorisation, boundaries and identity. A qualitative research design was used. Six nursing managers attended ten leadership coaching sessions over ten weeks. Field notes and reflective essays were analysed using systems psychodynamic discourse analysis. The findings indicated clarity and authorisation in the participants' primary task and normative roles; anxiety and de-authorisation in their experiential and phenomenal roles; anxiety in boundary management related to the misuse of power by others; and the continuous exploration of their leadership role identity towards achieving integration. Participants' learning experiences were evaluated in terms of criteria for organisational learning, after which a general hypothesis was formulated. Opsomming Die meestal liniêre en meganistiese aard van die verpleegbestuursrol is vinnig besig om na 'n meer dinamiese en sistemiese rol te verander. Die verandering behels taak- en mensbestuur binne 'n steeds veranderende organisasie-identiteit, waar 'n verskeidenheid rolle opgeneem word, die self en ander in 'n komplekse matrikssisteem bemagtig word, en waartydens bewuste en onbewuste sielkundige grense in en tussen botsende sisteme bestuur word. Die doel van hierdie studie was om die sisteem-psigodinamiese leerervaringe van verpleegbestuurders tydens leierskapafrigting te beskryf. Die afrigtingstaak was om leergeleenthede aan die individuele leier beskikbaar te stel vir die ontwikkeling van insig in bewuste en onbewuste leierskapsdinamika in terme van angs, taak, rol, outoriteit, grense en identiteit. 'n Kwalitatiewe navorsingsontwerp is gebruik. Ses verpleegbestuurders het tien leierskapafrigtingsessies oor tien weke bygewoon. Veldnotas en besinnende opstelle is deur middel van sisteem-psigodinamiese gespreksanalise ontleed. Die bevindinge dui op duidelikheid oor en bemagtiging in hulle primêre taak en normatiewe rol; angs en ontmagtiging in hulle ervarings- en fenomenale rolle; angs in grenshandhawing wat verband hou met magsmisbruik deur andere; en die voortdurende ondersoek en integrasie van leierskapsrolidentiteit. Deelnemers se leerervarings is na aanleiding van kriteria vir organisasieleer geëvalueer, waarna die algemene hipotese geformuleer is.